2015
DOI: 10.1016/j.virol.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Structures of minute virus of mice replication initiator protein N-terminal domain: Insights into DNA nicking and origin binding

Abstract: Members of the Parvoviridae family all encode a non-structural protein 1 (NS1) that directs replication of single-stranded viral DNA, packages viral DNA into capsid, and serves as a potent transcriptional activator. Here we report the X-ray structure of the minute virus of mice (MVM) NS1 N-terminal domain at 1.45 Å resolution, showing that sites for dsDNA binding, ssDNA binding and cleavage, nuclear localization, and other functions are integrated on a canonical fold of the histidine-hydrophobic-histidine supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…If these were considered, then the metal-binding range would increase to include Hg 2+ , Ca 2+ , Cd 2+ , and Cu 2+ . This promiscuity in divalent metal-binding is consistent with observations made with several HUH endonucleases, such as the TrwC relaxase, which can bind to Cu 2+ , Ni 2+ , and Zn 2+ [15] and the MVM NS1 protein, which can bind to Co 2+ , Cu 2+ , Ni 2+ , Mg 2+ , Mn 2+ , and Zn 2+ [16].…”
Section: Prediction Of the Sirv1 Rep Metal-binding Sitesupporting
confidence: 89%
See 1 more Smart Citation
“…If these were considered, then the metal-binding range would increase to include Hg 2+ , Ca 2+ , Cd 2+ , and Cu 2+ . This promiscuity in divalent metal-binding is consistent with observations made with several HUH endonucleases, such as the TrwC relaxase, which can bind to Cu 2+ , Ni 2+ , and Zn 2+ [15] and the MVM NS1 protein, which can bind to Co 2+ , Cu 2+ , Ni 2+ , Mg 2+ , Mn 2+ , and Zn 2+ [16].…”
Section: Prediction Of the Sirv1 Rep Metal-binding Sitesupporting
confidence: 89%
“…Most of the differences occur on both ARV sequences, where there is a stretch of positively charged sequences ranging from Lys‐46 to Lys‐57, which is more pronounced in ARV2 (K 46 KGKKKRKRKTK 57 ), precedes the putative DNA binding region described previously, and is not present in the other sequences. A similar but shorter stretch of basic amino acids occurs in the MVM , HboV , and AAV5 Rep proteins , and forms a loop, which inserts in the major groove of the 26‐mer dsDNA as seen in the AAV5 Rep197‐26 mer dsDNA complex structure. Although it is plausible that these ARV basic residues may also form a loop, a definitive answer can only be provided upon structural characterization of the ARV proteins.…”
Section: Resultsmentioning
confidence: 95%
“…Mutation of the two histidine residues (H115 and H117) confirmed their nicking function. A study of the structure of the MVM NS1 OBD also revealed conserved residues with DNA binding and nicking activities (45), highlighting the importance of the confirmed DNA binding and nicking residues of the HBoV1 NS1 OBD.…”
Section: Discussionmentioning
confidence: 96%
“…These functions are known to include endonuclease and helicase activity [38]. Unlike Apoptin, NS1 has a partial X-ray crystal structure, which has demonstrated that the protein has a more distinct structure of alpha helices and beta sheets, making it the only protein discussed in this review with distinctly folded domains [39,40]. NS1 is also known to self-associate, although the exact size of these oligomers is still unclear [41,42].…”
Section: Ns1mentioning
confidence: 99%